Անձնական հիշողությունից հանրային հիշողություն. ՀՊԹ երկու լուսանկար-տոհմածառի մշակութային կենսագրություն - Կարապետյան, Նելլի (Հայաստանի պատմության թանգարան)
The article considers the way of transformation of objects from a place of personal memory to a public one, using the example of two objects from thecollection of History Museum of Armenia. The first is a family tree with family members’ photos, the second is another version of a family tree on a large faience plate. They are unique “places of memory” where the experience, profession and everyday life of the families are summed up. The main issue is to consider the semantic and functional transformations of these objects as a result of museumization. The subject of the study, includes three layers: a photograph, a family tree and a museum object. As all of them are in the context of memory, the article addresses the study of memory, the museumization of the memory medium, and since the samples are family trees, it is also refers to the cross-generational study, emphasizing the role of photography in this matter. В статье рассматривается путь превращения предметов из места личной памяти в общественное на примере двух предметов из коллекции Музея истории Армении. Первое – родословное древо с фотографиями членов семьи, второе – родословное древо на большой фаянсовой тарелке. Последние являются уникальным «местом памяти», где суммируются опыт, профессия и повседневная жизнь семей. Основной вопрос заключается в рассмотрении смысловых и функциональных трансформаций этих объектов в результате музеефикации. Предмет исследования включает в себя три слоя: фотография, генеалогическое древо и музейный предмет. Поскольку все они находятся в контексте памяти, статья посвящена изучению памяти, музеефикации носителя памяти, а поскольку образцы являются генеалогическими деревьями, она также относится к межпоколенческому исследованию, подчеркивая роль фотографии в этом вопросе.
Keywords: Մշակութային մարդաբանություն